2022
DOI: 10.1021/acs.bioconjchem.2c00309
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescent Biosensor Based on Self-Assembled Fluorescent Gold Nanoparticles and Duplex-Specific Nuclease-Assisted Signal Amplification for Sensitive Detection of Exosomal miRNA

Abstract: The sensitive detection of cancer-associated exosomal microRNAs shows enormous potential in cancer diagnosis. Herein, a ratiometric fluorescent biosensor based on self-assembled fluorescent gold nanoparticles (Au NPs) and duplex-specific nuclease (DSN)-assisted signal amplification was fabricated for sensitive detection of colorectal cancer (CRC)-associated exosomal miR-92a-3p. In this biosensing system, the hairpin DNA modified with sulfhydryl and fluorescent dye Atto-425 at both ends is conjugated to fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The hairpin opened in the presence of the miRNA to form the hybrid, and then exogenous, duplex-specific nuclease enzyme was added to degrade the DNA strand of the hybrid RNA-DNA duplex and release the miRNA to react with further DNA hairpins. This strategy used a simpler enzyme-based catalytic cycle, resulting in an improved limit of detection of 45 fM, and the authors also demonstrated miR-92a upregulation in serum exosomederived samples from colorectal cancer patients [37].…”
Section: Fluorescent Mirna Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hairpin opened in the presence of the miRNA to form the hybrid, and then exogenous, duplex-specific nuclease enzyme was added to degrade the DNA strand of the hybrid RNA-DNA duplex and release the miRNA to react with further DNA hairpins. This strategy used a simpler enzyme-based catalytic cycle, resulting in an improved limit of detection of 45 fM, and the authors also demonstrated miR-92a upregulation in serum exosomederived samples from colorectal cancer patients [37].…”
Section: Fluorescent Mirna Biosensorsmentioning
confidence: 99%
“…Sun et al [37] employed a similar strategy to detect miR-92a, a biomarker of colorectal cancer, in serum exosomes. This method also involved an amplification cycle, in this case hairpin DNA probes labelled with an ATTO-425 fluorophore were attached to gold nanoparticles.…”
Section: Fluorescent Mirna Biosensorsmentioning
confidence: 99%
“…A specific antibody with a label can identify the cleaved structure and interpret the structure using methods such as electrochemistry [112]. It has been shown that this duplex-specific nuclease approach can be used in conjunction with fluorescence [113,114], surface plasmon resonance [115], or SERS [116] for the identification of signals in other ways.…”
Section: Enzyme-dependent Biosensingmentioning
confidence: 99%
“…This tool represents a potential innovative and specific system for CRC diagnosis. 139 Prussian blue NP (PBNP)-based fluorescent nanoprobes represent another type of biosensor for the diagnosis of CRC. PBNPs exploit the quenching ability to fluorophores to evaluate miR-92a and miR-21 levels, crucial CRC biomarkers.…”
Section: Mirna-nps In Crc Theranosticsmentioning
confidence: 99%